Erratum to: Physical fitness performance of young professional soccer players does not change during several training seasons in a Spanish elite reserve team: club study, 1996-2013 - Los Arcos, A.; Martins, J. (The Journal of Strength and Conditioning Research, 2018)
In the article, "Physical Fitness Performance of Young Professional Soccer Players Does not Change During Several Training Seasons in a Spanish Elite Reserve Team: Club Study, 1996-2013"1, which appeared in Volume 32, Issue 9 of the Journal of Strength and Conditioning Research, the institution approval information should appear as "The study was conducted according to the Declaration of Helsinki of 2013 and in agreement with the guidelines of the Institutional Review Committee of the Sports and Youth Institute of Navarre" instead of "The study was conducted according to the Declaration of Helsinki and was approved beforehand by the University of the Basque Country."